Comparative Study for the Levels of Trace Elements in Water from Southern Part of Iraq during 1996 – 2010 - Muayad H.Mohammed (University of Thi-Qar Journal of Science, 2019)
A comparative study for the levels of trace elements in water from southern part of IRAQ for the periodof time 1996 to 2010 was carried out to investigate the quality of waters. The study is based on the chemicalanalysis of trace elements: Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn. For subsurface water samples covered 12stations along Al-Izz , Tigress, Euphrates, Shatt Al-Arab, Khor Al-Zubair, Shatt Al-Basrah and Main OutletDrainage (MOD) rivers. Spectrophotometry was adopted for this analysis. The results showed that levels oftrace elements were between those for dissolved phase and particular matter of water in region whichnormally analyzed by atomic spectrometer. Trace elements concentrations reported by this study were higherthan allowed levels by WHO and IRPR without any classification of the phase studied. Fluctuation ofelements concentrations in the area attributed to metal input as well as geochemical and hydrologicalcharacteristics of the water.